2012
DOI: 10.2174/157489312803900965
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Systems Biology of Malaria Parasites Plasmodium

Abstract: Malaria is a serious infectious disease that causes over one million deaths yearly. It is caused by a group of protozoan parasites in the genus Plasmodium. No effective vaccine is currently available and the elevated levels of resistance to drugs in use underscore the pressing need for novel antimalarial targets. In this review, we survey omics centered developments in Plasmodium biology, which have set the stage for a quantum leap in our understanding of the fundamental processes of the parasite life cycle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 199 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…These include single cell technologies for genome sequencing and transcriptomic analyses, genotyping, and whole genome sequencing from dried blood spot samples. In addition, further comparative genomics [ 177 ] among all Plasmodium species infecting humans as well as those infecting nonhuman primates should identify key pathways in host switching. Genomic analysis of longitudinal samples will allow for the identification of population structure changes associated with changing epidemiology and emerging drug resistance.…”
Section: Technology and Its Application To Malaria Biologymentioning
confidence: 99%
“…These include single cell technologies for genome sequencing and transcriptomic analyses, genotyping, and whole genome sequencing from dried blood spot samples. In addition, further comparative genomics [ 177 ] among all Plasmodium species infecting humans as well as those infecting nonhuman primates should identify key pathways in host switching. Genomic analysis of longitudinal samples will allow for the identification of population structure changes associated with changing epidemiology and emerging drug resistance.…”
Section: Technology and Its Application To Malaria Biologymentioning
confidence: 99%
“…Other functional studies have shown a set of genes that are critical for the sexual development and now serve as canonical markers of gametocytogenesis [PF3D7_1302100 (Pfg27), PF3D7_0406200 (Pfs16), PF3D7_0935600 (Pfgig), PF3D7_1216500 (Pfmdv-1), PF3D7_0935400 (Pfgdv)] (Josling and Llinas, 2015). Recent studies have observed a transcription factor pfap2-g (PF3D7_1222600), belonging to the Apetala (Api2) family of transcription factors, as the master regulator of gametocytogenesis (Cai et al , 2012; Sinha et al , 2014). In P. falciparum , the DNA-binding protein PfAP2-G has been shown to have a strong correlation with gametocytogenesis.…”
Section: Introductionmentioning
confidence: 99%